Desenvolvimento de um modelo matemático simplificado da irrigação por sulcos abertos em declive - Levien, Sérgio Luiz Aguillar (1985)
An algebraic model of furrow irrigation was herein developed. This model can be used to predict the performance of a sloping, free draining,furrow irrigation system, based on the solution of continuity equation under the hypothesis of normal depth. [...]